Currículos-experimentações: o que podem os encontros dos/com os bebês? - Touret, Fernanda Binda Alves (2023)
Amidst a journey under a research mode, we navigated open waters with an inventive vessel, set adrift in the becomings of infants in the territories of Early Childhood Education. We bet on the invention of infants within a process of problematization, which moves away from the idea of solving problems and representation (Kastrup, 2001). The research was conducted at a Municipal Center for Early Childhood Education in the city of Vitória/ES, involving infants, teachers, and educators, with cartography as a methodology to track their inventive processes in the daily life of early childhood education. Understanding curricula as territories of encounters, we engaged in inventive experiments with/for infants to navigate a map open to possibilities (Deleuze; Guattari, 2011b), throughout an intensive branching of inventive possibilities. The study shifts to problematize the curricular movements and inventive experiments infants undertake in the territories of early childhood education. Its main objective is to problematize the inventive processes of infant experimentation, highlighting rhizomatic curricular flows through multiple written and visual statements within this collective. Amid research-flights, we proposed a pedagogy that "drinks itself" and wanders with infants, to raise other modes in their unique languages and bodily expressions, breaking through space-times and exploding joys in the body alongside curriculum-experimentation movements.